"Exploring Prosthetic Eye Materials: Trends, Challenges, and Future Directions"-A Review Study - Tyagi, Trisha; Kaur, Sandeep; Singh, Shubhanshi; Bhatt, Akrisht; Dosad, Pooja (Journal of Neonatal Surgery, 2025)
The goal of the significant developments in prosthetic eye material formulation is to improve the functional and cosmetic outcomes for patients who requires ocular prosthesis. The current trends, hindrances, and conceivable directions in prosthetic eye materials are discussed in this review. Due to their ready accessibility, ease of customization, and affordability, conventional materials such as lead crystal and acrylic resin have been broadly utilized. But discovery of new biomaterials has been driven by the demand for better biocompatibility, permanency, and patient comfort. Greater flexibility and less of the issues such as infection and inflammation are offered through newer advances in silicone elastomers, 3D printing, and nanomaterials. Despite such advances, challenges still remain, including the requirement to take full advantage of material properties, budgetary constraints, and limited convenience within low-resource environments. By presenting recent advances in biocompatible coatings, antimicrobial technology, and personalized manufacturing techniques, this paper demonstrates the importance of multidisciplinary collaboration to address these challenges. To transform ocular prosthetics, it also puts forth potential future applications, including the addition of bioengineered solutions and intellectual materials. This review is to aid researchers, physicians, and manufacturers in the commencement of future prosthetic eye materials that maximize patient outcomes and quality of life by presenting a comprehensive review of the field.